2014
DOI: 10.1038/srep06299
|View full text |Cite
|
Sign up to set email alerts
|

First Fatality Associated with Elephant Endotheliotropic Herpesvirus 5 in an Asian Elephant: Pathological Findings and Complete Viral Genome Sequence

Abstract: Infections of Asian elephants (Elephas maximus) with elephant endotheliotropic herpesvirus (EEHV) can cause a rapid, highly lethal, hemorrhagic disease, which primarily affects juvenile animals up to the age of four years. So far, the majority of deaths have been attributed to infections with genotype EEHV1 or, more rarely, EEHV3 and EEHV4. Here, we report the pathological characteristics of the first fatality linked to EEHV5 infection, and describe the complete viral DNA sequence. Gross post-mortem and histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 30 publications
8
50
0
Order By: Relevance
“…Based on the finding of multiple different EEHV types in four of the five adult African elephants studied here, it seems clear that prior infection by one EEHV species does not necessarily provide protection against the establishment of persistent infection by one or more of the other EEHV types, possibly even including infection by a second strain of the same EEHV type, but it could mitigate the pathological symptoms and disease severity of subsequent primary infections by other EEHV strains or types. On the other hand, the majority of lethal disease cases in young Asian elephants, whether under human care in North America and Europe (19) or within Asian countries such as India (11), Thailand (20), Cambodia (35), and Laos (36), have been caused by a variety of different strains of EEHV1A or EEHV1B (3,7), together with two examples of EEHV4 (18) and one example of EEHV5 (10,23). This suggests that the two subgroups of EEHV1 and probably also EEHV4 and EEHV5 originated in Asian elephants (9,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the finding of multiple different EEHV types in four of the five adult African elephants studied here, it seems clear that prior infection by one EEHV species does not necessarily provide protection against the establishment of persistent infection by one or more of the other EEHV types, possibly even including infection by a second strain of the same EEHV type, but it could mitigate the pathological symptoms and disease severity of subsequent primary infections by other EEHV strains or types. On the other hand, the majority of lethal disease cases in young Asian elephants, whether under human care in North America and Europe (19) or within Asian countries such as India (11), Thailand (20), Cambodia (35), and Laos (36), have been caused by a variety of different strains of EEHV1A or EEHV1B (3,7), together with two examples of EEHV4 (18) and one example of EEHV5 (10,23). This suggests that the two subgroups of EEHV1 and probably also EEHV4 and EEHV5 originated in Asian elephants (9,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Although EEHVs have not yet been propagated in cell culture, a great deal of genetic analysis has been carried out directly on blood samples or necropsy tissue from cases of hemorrhagic disease, including the prototype strains for each of the six known major EEHV types and two other partially chimeric subgroups (3)(4)(5)(6)(21)(22)(23)(24). The results showed that, compared to all other known mammalian herpesviruses, they form a single novel clade, in which EEHV1 and EEHV6 plus EEHV2 and EEHV5 cluster together into two distinct lineages of an AT-rich branch, whereas EEHV3 and EEHV4 form a separate, highly diverged GC-rich branch.…”
mentioning
confidence: 99%
“…Surveillance for subclinical infection was recently conducted on healthy captive and semi-captive Asian elephants in southern India, where results revealed that the most common viral type to be shed from animals was EEHV5 (Stanton et al, 2014). However, the number of fatal cases associated with EEHV5 infection was relatively low, compared to its high prevalence in healthy/subclinical elephants (Latimer et al, 2011;Atkins et al, 2013;Stanton et al, 2014), with only one fatal case reported in association with EEHV5 infection (Denk et al, 2012;Wilkie et al, 2014). These results were similar to those from our study, where none of the fatal cases were due to EEHV5 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the most common type is EEHV1, which has two closely related subgroups; EEHV1A and EEHV1B . EEHV1, EEHV3, EEHV4 and EEHV5 have been reported as the causative agent for mortalities of Asian elephants (Richman et al, 1999;Garner et al, 2009;Latimer et al, 2011;Wilkie et al, 2014) whereas EEHV2, EEHV3, EEHV6 and EEHV7 are mainly found in African elephants (Richman et al, 1999;Latimer et al, 2011;Zong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from the pelleted virus35. Paired-ended, 150 nucleotide sequence reads were generated for the strain C500 BAC clone and the reconstituted virus by using a MiSeq DNA sequencer running version 2 chemistry (Illumina) and assembled by using methods described previously36. The sequence of the TR region of strain WC11 was derived as part of a similar project.…”
Section: Methodsmentioning
confidence: 99%